Kajian Tingkat Kontaminasi Pada Kultur Jaringan Tanaman Porang - Tsani Nur Khoiriah Sutarsih; Zulaikhok Nuraini; Kiki Novia Andriani; Dyah Wulandariningtyas; Farhan Wirayudha; Wuryantoro (Universitas Merdeka Madiun, 2022)
The natural growth period of porang plants is only about four months in a year, allowing them to be planted in the off-season. For this purpose, the availability of seeds is a problem that needs to be solved. One technique that can be used to produce porang seedlings out of season and does not take long is the tissue culture technique. This technique has the advantage of using selected lines, free of pests and diseases, and can produce many seeds quickly. However, the problem that often occurs is its sensitivity to disease contamination during the culture-making process. Laboratory quantitative research in the form of experiments using an empirical approach is used in this study. The treatments used were the use of implant origin, namely: (1)upper tuber shoots, (2) bottom tuber shoots, and (3 )buttom tuber skin shoots. The callus formation in this experiment was still low due to the high level of fungal contamination. Estimated that the fungus carried out by the origin of the tubers and laboratory conditions are less sterile. Porang plant tissue culture should use specially grown shoots that are free of pests and diseases. Keywords—: upper tuber shoots, buttom tuber shoots, tissue culture, “porang”